New Direction for Green Economics Through The Development of Global Islamic Economics: A Bibliometric Analysis - Harizah, Siti; Supriyanto, Achmad Sani; Masyhuri; Mahsun, Moch (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
Green economics is the study of sustainable economic transformation with environmentally friendly principles. Many studies that position green economics discuss the energy transition and the influence of technological and scientific developments, including from the perspective of policy studies from the political realm. However, of the many articles, only a few specifically discuss topics with a legal perspective and Islamic economic principles. Even though the basic foundation of maqashid sharia is an essential element in protecting the environment and being sustainable, this research aims to see the extent of Islamic studies in the green economics sector. From the results of the bibliometric analysis, researchers also see many gaps between the green economy and the Islamic economy, one of which is in terms of sharia management, halal industry, sharia finance, social finance, sharia management still focuses on energy transformation and even though the governance side still has uncertain benchmarks. Meanwhile, the halal industry only discusses the term green supply chain. From various existing studies, the research only focuses on sustainable economic theory, while the discussion on Islamic-based green economics is not very in-depth and specific.